Experimental research on ethyl acetate as novel oxygenated fuel in the spark-ignition (SI) engine. Issue 1 (31st December 2023) - Çakmak, Abdülvahap; Kapusuz, Murat; Özcan, Hakan
ABSTRACT: It is known that blending oxygenated fuels to gasoline can increase knock resistance of the fuel and reduce exhaust emissions. In this experimental research, ethyl acetate as a new and renewable oxygenated fuel which is produced through the reaction of ethanol with acetic acid was added to base gasoline at 5% (E5) and 10% (E10) volume ratios to investigate its effect on engine performance and exhaust emissions. For this, a single-cylinder and four-stroke SI engine was utilized, and engine experiments were carried out under low, medium, high and full load at a constant engine speed of 1500 rpm. The potential for the ethyl acetate as oxygenated fuel was also further investigated by distillation tests. In addition, a fuel cost analysis based on brake specific fuel consumption and fuel price was performed. Results revealed that E5 and E10 displayed superiors in terms of CO and HC emissions to base gasoline. It was determined that oxygen content in ethyl acetate led to decrease in CO and HC emissions by 54.5% and 50.1%, respectively. However, NOX emissions dramatically increased by 81.1% with fuel blends operation and engine performance parameters such as brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE) deteriorated. Furthermore, the fuel economy analysis showed that 5 vol.% and 10 vol.% ethyl acetate blends with base gasoline presented averagely 38.9% and 84.5% higher fuel cost relative to gasoline.